Zeus on the stud farm? : against a Homeric instance of attractio relativi - Probert, P (Brill, 2014)
The genitive ἧς at Iliad 5.265 is sometimes considered due to attractio relativi. Alternatively it is taken as a partitive or ablatival genitive, or emended. The question matters for Greek linguistic chronology because uncontroversial attractio relativi is not found until the fifth century BC. This paper addresses the question via a fresh examination of the syntax and sense of lines 265–9. The linguistically most plausible views are: (i) we should not understand εἰσίν with τῆς γάρ τοι γενεῆς, nor punctuate strongly after 267; (ii) ἧς should stand, and is a partitive genitive; (iii) οὕνεκα means 'because'. The resulting interpretation implies that Zeus accessed some pre-existing stock of horses, otherwise unknown to Greek literature. For many scholars this is a fatal objection to ἧς as a partitive genitive, with some concluding that ἧς is due to attractio relativi or corrupt, and others that ἧς is an 'ablatival genitive' (a suggestion that does not solve the perceived problem). This paper defends the partitive genitive analysis on the grounds that Homeric audiences could easily have imagined Zeus getting the horses from some pre-existing stock. Parallels support the plausibility of this background assumption. We do not have a Homeric instance of attractio relativi.